Measurement of Ti-50(n, alpha)Ca-47 reaction cross sections for 13.6- to 14.9-MeV neutrons - Subasi, M; Bostan, M; Erduran, MN; Durusoy, A; Gultekin, E; Tarcan, G; Ozbir, Y (AMER NUCLEAR SOCIETY, 1996)
Experimental setup and related measurements for determining precise neutron energy and flux and methods utilized for data acquisition and reduction with the recent results of Ti-50(n, alpha)Ca-47 cross-section measurements performed between 13.6 and 14.9 MeV are presented. The results are also compared with calculations based on the statistical model.
Keywords: ENERGY; Nuclear Science & Technology